(untitled) (Journal of Pharmaceutical Negative Results, 2014)
Aim: To study the air growth promoting effect of roots of G. glabra and Z.mauritiana in androgen (testosterone) induced male pattern baldness (androgenicalopecia). Materials and Methods: Animals were divided into four groups andthey were attempted to made alopecic by treatment with testosterone for 3 weeks.Group 1 (control), 2 (standard), 3 and 4 animals (test) were also treated topically withvehicle, finasteride and ethanolic extract of Z. mauritiana roots and G. glabra rootsrespectively. Animals were observed for signs of alopecia and after treatment periodone animal from each group was euthanized randomly and the skin sections from thetreated area was examined for changes in follicular morphology. Statistical Analysis:Statistical analysis of data was carried out by one‑way ANOVA. Using Instat version 2.1software. Results: The Group 1, 3 and 4 animals develop alopecia and their skin sectionalso shows bulbous and miniaturized hair follicles and prominent sebaceous gland whileGroup 2 (standard antiandrogenic drug finasteride treated) animals does not developalopecia and skin samples also shows well‑formed follicles and normal sebaceous gland.Conclusion: This experiments shows incapability of ethanolic extract of Z. mauritianaand G. glabra combating androgenic alopecia